Reinvigorating disengaged staff (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. According to a survey conducted across 142 countries by Gallup, just 13% of employees worldwide are engaged at work. Symptoms of disengagement may include apathy, poor communication, absenteeism, missed deadlines, and cynicism. So, how does this translate into day-to-day experiences in the workplace? What does withdrawal mean for businesses more broadly, and what can you do to revitalise employee engagement? In this track, we'll cover How to determine who's losing motivation Identifying problems with engagement Diagnosing engagement issues, and Communicating effectively with disengaged employees Learning Objectives Learn how to determine who's losing motivation Learn how to identify problems with engagement Learn how to diagnose engagement issues, and Learn how to communicate effectively with disengaged employees.